Exchange rate pass-through to inflation in Nigeria - Abiodun S. Bada; Ajibola I. Olufemi; Inuwa A. Tata; Idowu Peters; Sani Bawa; Anigwe J. Onwubiko; Udoko C. Onyowo (CBN Journal of Applied Statistics, 2016)
Concerns about the magnitude and length of exchange rate pass-through to consumer prices have increased in many developing countries in view of its profound implications on price and exchange rate stability as well as the macroeconomic policy environment. This paper examines the exchange rate pass-through effect at the aggregate level into import and consumer prices in Nigeria for the period 1995Q1 - 2015Q1. Utilizing the Johansen approach to cointegration and a vector error correction methodology, the paper found the exchange rate pass-through into Nigeria's CPI inflation to be incomplete. The long run pass-through elasticities were found to be 0.24 and 0.30 for the baseline and alternative models. The effect was discovered to be higher in import than in consumer prices, implying that the pass-through effect declines along the pricing chain. These findings were useful in the design and implementation of monetary and exchange rate policies by the Central Bank of Nigeria.
Keywords: C32; E31; F31; O55; 330; Exchange rate pass-through; Prices; Cointegration; Vector Error Correction; Impulse response